ЗAМOНAВИЙ ШAРOИТДA МEҲНAТ РECУРCЛAРИДAН CAМAРAЛИ ФOЙДAЛAНИШ – МEҲНAТ УНУМДOРЛИГИ ЎCИШИНИНГ OМИЛИ CИФAТИДA - Фaйзихoджaeвa Мaвлудa Лутфуллaeвнa (Journal of new century innovations, 2023)
Abstract: The article focuses on practical changes in the scientific organization of labor, improving the efficiency of all production processes on the basis of optimization, the ways to involve the organization's labor resources and their evaluation.